Proteomics insights into medullary sponge kidney (MSK) disease: review of the recent results of an Italian research collaborative network. - Simona Granata; Maurizio Bruschi; Giovanni Candiano; Valeria Catalano; Gian Marco Ghiggeri; Giovanni Stallone; Gianluigi Zaza (Karger Publishers, 2022)
Background: Medullary sponge kidney (MSK) disease is a rare and neglected congenital condition typically associated with nephrocalcinosis/nephrolithiasis, urinary concentration defects and cystic anomalies in the precalyceal ducts that, although sporadic in the general population, is relatively frequent in renal stone formers. The physiopathologic mechanism associated with this disease is not fully understood and omics technologies may help to address this gap. Summary: The aim of this review is to provide an overview of the current state of the application of proteomics in the study of this rare disease. In particular, we focused on the results of our recent Italian collaborative studies that, analyzing the MSK whole and extracellular vesicles urinary content by mass spectrometry, have displayed the existence of a large and multifactorial MSK-associated biological machinery and identified some main regulatory biological elements able to discriminate patients affected by this rare disorder from those with idiopathic calcium nephrolithiasis and autosomal dominant polycystic kidney disease (including laminin subunit alpha 2, Ficolin 1, Mannan-binding lectin serine protease 2, Complement component 4-binding protein β, sphingomyelin, ephrines). Key messages: the application of omics technologies have provided new insights into the comprehension of the physiopathology of the MSK disease and identified novel potential diagnostic biomarkers that may replace in future expensive and invasive radiological tests (including CT) and select novel therapeutic targets potentially employable, whether validated in a large cohort of patients, in the daily clinical practice.